(untitled) (Journal of Environmental Microbiology and Toxicology, 2015)
Polyethylene glycols (PEGs) are employed in numerous sectors. PEGs are nephrotoxic and their biodegradation by microbes could be a potential tool for bioremediation. Numerous bacterial growth studies neglect primary modelling even though modelling exercises can reveal important parameters. In this work we modelled the growth of the sludge microbes on PEG 600 based on available published work in the literature using several growth models such as modified logistic, modified Gompertz, modified Richards, modified Schnute, Baranyi-Roberts, Von Bertalanffy, Huang and the Buchanan three-phase linear model. Statistical analysis results indicated that the modified Gompertz model was the best with highest adjusted R2, lowest RMSE and AICc values and Bias and Accuracy Factor values closest to unity. The results from this work can be used in the further optimization works of this process in the future.